Intellectual Capital, Financial Performance and Market Performance : Evidence From High IC Intensive Company in Indonesia - Hermawan, Sigit (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
This study aims to examine and analyze the effect of intellectual capital on firm financial performance and market performance. The company studied is the financial sectors High IC Intensive companies listed in Indonesian Stock Exchange (IDX). 52 companies in period of 2014- 2017 are chosen for sample. Independent variable used are the intellectual capital measured using VAIC and MBIC, while the data analysis technique used double linier regression. The results showed that the intellectual capital (VAIC) effect the company's financial performance Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) and market performance. Meanwhile, intellectual capital (MBIC) affect the company's financial performance Return On Assets (ROA), Earning Per Share (EPS), but it didn't effect the market performance.